Saturated fat, sodium and sugar in selected food items : a comparison across six European countries - Ferreira, Jennifer Marie Tretter (2018)
ABSTRACT - Introduction: The amount of sodium, sugar and saturated fat in foods, when consumed in excess can lead to an unhealthy diet, and ultimately, risk for Noncommunicable diseases (NCDs). The processing of food contributes to the overconsumption of these nutrients. Objectives: To determine the characteristics of distribution for sodium, sugar and/or saturated fat in the commonly consumed food products of cheese, bread, and ready-to-eat breakfast cereal (RTEBC) and to compare across countries. Methods: For the countries of Belgium, Norway, Poland, Portugal, Serbia and Sweden, a convenience sample of cheese, bread and RTEBC was gathered from each country´s national food composition table, made available through the online databases of EuroFIR´s FoodEXplorer, Matveretabellen, Nubel and PortFIR. Amounts of sodium, sugar and saturated fat were registered. After descriptive statistics, Mann-Whitley U or Kruskal-Wallis tests (with multiple comparison, if necessary) were applied to determine statistical differences across countries. Results: For the cheese group and saturated fat, Belgium presented a distribution statistically different from Portugal and Sweden (p<0.01). Norway´s distribution was significantly different from Portugal (p<0.05). Highest distribution levels were in Belgium, lowest in Portugal. For the bread group and sodium, Norway´s distribution was significantly different from Poland, Belgium and Serbia (p<0.001); Portugal´s from Belgium and Serbia (p<0.05); and Sweden´s from Belgium and Serbia (p<0.01). Lowest medians were Portugal (290 mg/100 g), Norway (316 mg/100 g) and Sweden (354 mg/100 g); highest were Belgium (498 mg/100 g) and Serbia (510 mg/100 g). In RTEBC samples and sugar, there is evidence that distributions are not equal across countries (p<0.05). Lowest median was Serbia (6 g/100 g); highest was Belgium (21.8 g /100 g). Conclusion: In general, saturated fat in cheese, sodium in bread and sugar in RTEBC are significantly different in Belgium, Norway, Poland, Portugal, Serbia and Sweden. Further investigation is needed to determine how much these variations contribute to excess intake. Comparison of nutrient amounts in similar foods across countries provides an opportunity to explore differences in food composition, regional products, food legislation and other forms of healthy product promotion in order to benefit consumers.